Seroprevalence of anti-HBs antibodies and the need for booster vaccination in children under 5 years of age born to HBsAg-negative mothers - Jannatin Nisa Arnindita; Muhammad Miftahussurur; Bagus Setyoboedi; Juniastuti (Asian Pacific Journal of Tropical Medicine, 2021)
Objective: To determine the proportion of HBV surface antigen (anti-HBs) antibody positive children under five years of age born to HBsAg-negative mothers and to analyze the possible related factors following implementation of a hepatitis B vaccination program for infants in Indonesia 22 years ago. Methods: Blood samples were taken from children under five years of age born to HBsAg-negative mothers who have completed primary vaccination series. Anti-HBs antibodies were determined by using rapid test. Data of age, gender, nutritional status, vaccination timing or vaccination compliance, and booster vaccination were collected from vaccination card. Results: Ninety children were enrolled, consisting of 47 females and 43 males with a mean age of 2.3 years. Twenty two (24.4%) children received booster vaccine between 18 and 24 months and 55 (61.1%) were anti-HBs positive. Among factors of age, gender, nutritional status, compliance to vaccination and booster vaccine, only administration of booster vaccine was significantly associated with anti-HBs status (OR 5.45, 95% CI 1.45, 20.52). Children who received booster vaccine at age of 18-24 months were 5.45 times more likely to be anti-HBs positive than that of children who did not receive booster vaccine. Conclusions: Booster vaccine rate is low among children under 5 years of age but is associated with anti-HBs positivity. Booster vaccination may be required to improve anti-HBs seropositivity.